The Effectiveness of Al-MuhÄdastah Textbook to Improve Arabic Speaking Skills - Mahmudi, Ihwan; Maha, Marheni Br; Lubis, Zulfahmi; Silmy, Ahmad Nahidl; Zalzuli, Ahmad (Institut Agama Islam Negeri Curup, 2023)
This research aimed to develop a textbook called